The implications of lead firm sourcing strategies and value chain governance on suppliers and sector development: the case of the South African textile and apparel industry - Mkhabela, Vuyiswa (School of Economics, 2025)
This dissertation investigates the sourcing strategies and value chain governance of South African apparel retailers and their impact on the local textile and apparel manufacturing sector. Over the past three decades, value chain research has highlighted the crucial role of lead firms in coordinating production networks and shaping supplier relationships. However, little research has focused on the strategies of lead firms from the Global South, particularly in Africa's apparel industry. Through an integrated analysis of value chain governance, trade, and industrial policies, supplemented by case studies, this research examines the evolving sourcing strategies of South African retailers. Findings indicate that these strategies are influenced by strategic priorities, public value chain governance, global trends towards resilient supply chains, and supplier capabilities. Over the past 10-15 years, South African retailers have shifted from offshoring to nearshoring and reshoring, transitioning from transactional and captive governance to hierarchical and network-based models. The study demonstrates that hierarchical governance, marked by vertical integration, and network-based governance, characterized by partnerships, have distinct implications for supplier development and sectoral restructuring. This research contributes to the literature by providing insights into the sourcing strategies and value chain governance of lead firms in the Global South, highlighting the interaction between private sector practices and public policy in fostering industrial development.